Development of systemological model of the problem of structural and topological reengineering of large scale monitoring systems - Бескоровайный, Владимир Валентинович; Подоляка, Ксения Евгеньевна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper deals with developing the systemological model of the problem of structural and topological reengineering of large-scale monitoring systems. Based on the analysis of the life cycle stages of geographically distributed systems, the place of reengineering in the structure of the life cycle of large-scale monitoring systems was defined, the analysis of the factors that determine their efficiency was performed. Formalization of the description of large-scale monitoring systems has allowed to identify subsets of elements, relationships, topologies and properties that will be included and (or) excluded in the system re-engineering process. This allows to form a set of feasible system reengineering solutions. To reduce the reengineering problem complexity, a three-level scheme of its decomposition was proposed, the composition and the relation schematic of problem-related tasks by the input and output data were determined. This allows to create effective technologies for structural and topological reengineering. Practical application of the results obtained allows to reduce the time for solving reengineering problems, improve the quality of solutions through joint problem solving and on this basis improve the cost and functional characteristics of the restructured systems.